Phospholipase C δ2 Expression Characterizes the Neoplastic Transformation of the Human Gastric Mucosa - Marchisio, Marco (American Society for Investigative Pathology, 2001)
The expression, cellular distribution, and activity of PIP(2)-specific phospholipase C (PLC) in healthy human gastric-mucosa cells have been recently studied in our laboratories and a direct evidence for an almost exclusive expression of PLC β isoforms, with the exception of PLC β4, has been provided. These results addressed our attention to possible modification of PLC expression and activity during neoplastic transformation of the human gastric mucosa. In the present article we present results indicating that PLC δ2 is markedly expressed in type II intestinal metaplasia and in the adenocarcinoma whereas traces of other PLC isoforms were sometime detected. Interestingly, we found that type I intestinal metaplasia was in the majority of the cases PLC δ2-negative, but when expressed, this type of metaplasia generally considered as benignant, always evolved toward neoplastic transformation. These results therefore readdress the question of surveillance of the patients with type I intestinal metaplasia and suggest that PLC δ2 expression might be a possible marker of gastric malignant transformation.